Autoantibodies to gut hormone secreting cells as markers of peptide deficiency. Issue 5 (May 1983) - Jones, H W; Lendrum, R; Marks, J M; Mirakian, R; Bottazzo, G F; Sarson, D L; Bloom, S R
Abstract : Autoantibodies reacting with endocrine cells in the gastrointestinal mucosa were found by indirect immunofluorescence in 22 out of 268 sera (8.2%) obtained from patients with coeliac disease, Crohn's disease, ulcerative colitis, irritable bowel syndrome, and from subjects without bowel disease. A double immunofluorescence technique showed that the autoantibodies reacted with cells secreting gastric inhibitory polypeptide (glucose dependent insulinotropic polypeptide, GIP), secretin, somatostatin or enteroglucagon. Most sera contained antibodies against more than one cell type. Neither the presence of a particular antibody nor the pattern of antibody combinations appeared to be specific for any diagnostic category. The mean plasma GIP concentrations, however, both fasting and two hours after a test meal, were significantly lower in subjects with GIP cell autoantibodies. Thus gut hormone cell autoantibodies may be markers of impaired hormone secretion.